PRACTICAL USE OF NONMETALLIFEROUS RAW MATERIALS COPPER-NICKEL DEPOSITS - Liudmila I. Khudyakova; Svetlana S. Timofeeva (Юг России: экология, развитие)
Aim. Copper-nickel deposits are located all over the world. A large amount of nonmetalliferous raw materials is formed, when they are developed. It moves into dumps and creates environmental risks for the environment. In the dumps magnesium-containing rocks prevail, which must be disposed of. The purpose of the work is to study the possibility of their use in the production of building materials. Methods. The chemical analysis was carried out by gravimetry, photometry, and atomic-absorption spectroscopy. The mineral composition was studied using X-ray phase analysis. The mechanical parameters were determined on a test hydraulic press. Results. It is established that the crushed stone from magnesiumbearing rocks is of high quality and can be used as a large aggregate in the production of concretes. It is shown that the concrete, containing crushed stone from ultrabasic rocks - verlites show the most compression strength. The lowest values has ordinary concrete on granite crushed stone. The type of hardening conditions also affects the strength of the resulting material. Sand from the sifting of crushing rock mass has angular shape of the grains and a mineral composition as in the parent rock. This contributes to the design of a dense structure of concrete stone, which increases its strength by more than 10%. Main conclusions. The use non-metalliferous raw materials will reduce the volumes of waste rock formed during the development of mineral deposits. In this case, it is possible to obtain a finished commodity product - crushed stone from magnesium-containing rocks and sand from their crushing. This will solve environmental, economic problems, as well as produce the necessary building materials for their own needs.